The Role of Inositol Phosphate Multikinase (IPMK) in Time Restricted Feeding in Animal Model - Jung, Ik-Rak (J Endocr Soc, 2021)
Obesity is a major public health problem of the U.S. and is associated with diabetes, cardiovascular diseases and other diseases. Most research studies focus on excessive food consumption as the main cause of obesity. However, emerging data indicate that the timing of feeding can have significant effects on body weight and metabolism. Numerous studies in animals and small clinical studies in humans have shown that eating erratically over the 24 hour period or out of phase with the circadian rhythm predisposes toward weight gain, steatosis, dyslipidemia, insulin resistance and diabetes. Furthermore, studies indicate that restricting food intake to the active period synchronizes the circadian rhythm and metabolism, enhances weight loss and improves metabolic outcomes. Time restricted feeding (TRF) increases the amplitudes of clock gene expression and pathways mediating nutrient sensing and hepatic metabolism. However, the mechanisms mediating the effects of TRF are not fully understood. Here we characterized mice (10 week-old) fed a high-fat diet ad libitum (ALF) or from 7 pm to 7 am (TRF) for 2 weeks. The basal glucose production rate was similar between the two groups. Under hyperinsulinemic-euglycemic clamp, the glucose infusion rate (GIR) was significantly greater in TRF group compared to ALF group indicating an increase in insulin sensitivity. Using radioisotopic tracers, we demonstrated that the hepatic glucose production (HGP) was significantly reduced and the glucose disappearance rate was increased in TRF group compared to ALF group. Moreover, a biochemical analyses of liver tissues revealed that Inositol phosphate multikinase (IPMK) act as a key enzyme for inositol polyphosphate biosynthesis and play a role in insulin-, nutrient-, and energy-mediated metabolic signaling, was increased during TRF. Moreover, deletion of IPMK in hepatocytes decreased insulin stimulated AKT phosphorylation while increased lipid accumulation and gluconeogenesis. Importantly, hepatic deletion of IPMK attenuated the beneficial effects of TRF suggesting that IPMK in the liver may contributes to beneficial effects of TRF. Our findings provide the potential mechanism by which TRF confers the beneficial effects and may provide a novel therapeutic strategy for treating diabetes.